ANALYSIS OF THE REQUIREMENTS FOR DATA ANALYST AND DATA SCIENTIST POSITIONS IN THE LABOR MARKET - KULAZHENKO, VOLODYMYR; PIDHAINYI, DENYS (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The labour market in the field of data analytics was analysed in this article. Specifically, there were analysed the requirements for vacancies Data Analyst and Data Scientist. The analysis covered such job search platforms as Work.ua (Ukraine), Robota.ua (Ukraine), DOU (Ukraine), Djinni (Ukraine), The Muse (USA), Technojobs (France), Careerjet (Canada), Profesia (Czech Republic, Slovakia), Reed (UK).The study was consisted of 4 stages: semi-automated data collection, processing of key job requirements, data storage and structuring, and data analysis. Such tools as Python (streamlit, pandas, re) and AirTable were used in the study. The structure and style of job postings on job search sites were analysed. Patterns were discovered that could be used to derive key indicators. Algorithms for replacing missing data, such as work experience, were discovered. An application was developed to automate the process of analysing of the text of vacancies. The user interface was implemented using the Streamlit framework. A total of 1000 vacancies were collected for analysis. Of these, 586 were collected from Ukrainian sources, and the rest were from abroad.The research was based on the analysis of the following indicators: the frequency of vacancies by position (junior, middle, senior); the type of companies looking for Data Analyst or Data Scientist; the mode of work (offline, online and hybrid); the level of English proficiency; visualisation tools that the candidate should know; preferred programming language; desired database; requirements for office tools; requirements for knowledge of specialised libraries for data analysis and machine learning. All these indicators were quantitatively analysed and a conclusion was drawn. A table, that clearly demonstrates the researched trends, have been developed by authors.
Keywords: labour market; requirements for specialists; Data Analyst; Data Scientist